The determinants of hotel occupancy in Jamaica 2000-2006 - Ramjeesingh, Diaram (Central Bank of Barbados [St. Michael]BB, 2008)
Seeks to establish the primary determinants of hotel accupancy in Jamaica for the period January 2000 to December 2006. Establishes the argument that as government expansionary room policy continues, at a level ahead of current stopover demand, hoteliers will in the near future be forced to reduce prices, in order to sell excess room capacity.